The Teaching of Reading in Senior Secondary School - Pranata, Mohammad Sofyan Adi (International Journal of English Education and Linguistics (IJoEEL), 2019)
Reading English is an important skill that students need to learn. The teaching of reading in secondary school will help student to get a purpose for reading, focus on what they are learning, think actively as they read, monitor their comprehension, and review content and relate what they have learned to what they already know. In order to apply the strategies effectively in new instructional settings, teachers must have a clear understanding of the reading comprehension process and the natural reading strategies that commonly applied by our students. By knowing this, they can select and demonstrate appropriate reading strategies that their students need in reading the text.